Liquid epoxy resin composition for being used as mold underfill material for TSV
The liquid epoxy resin composition addresses heat dissipation and reliability issues in high-density semiconductor devices by using a formulation with silica and alumina fillers, carbon black, and an ion trapping agent, ensuring effective heat dissipation and preventing short circuits.
Patent Information
- Application Number
- JP2023114447
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-12
- Publication Date
- 2025-01-24
AI Technical Summary
Semiconductor devices with high-density wiring and multiple three-dimensionally stacked chips face issues with heat dissipation and reliability due to short distances between chips and wafers, leading to performance deterioration and increased risk of short circuits, particularly when using mold underfill materials with low thermal conductivity and high chloride ion content.
A liquid epoxy resin composition for mold underfill material comprising epoxy resin, hardening agent, silica and alumina fillers, carbon black, and an ion trapping agent, which provides thermal conductivity of 0.8 W/m·K or more and reduces chloride ion content to enhance heat dissipation and reliability.
The composition effectively dissipates heat and prevents short circuits in semiconductor devices, maintaining performance and reliability even with short distances between chips, as demonstrated by improved thermal conductivity and reduced chloride ion concentration.
Smart Images

Figure 2025011966000006 
Figure 2025011966000007 
Figure 2025011966000008
Abstract
Description
[Technical field]
[0001] The present invention relates to a liquid epoxy resin composition for use as a mold underfill material for TSV. [Background technology]
[0002] In recent years, in order to further improve the performance of electronic devices, there is a demand for higher density wiring on chips in the electronic components that make up the electronic devices. However, the wiring density per unit area of the chip can be increased by further miniaturizing the wiring, which is approaching its limit. Therefore, it has become common to further increase the wiring density per unit area of the chip by stacking multiple chips three-dimensionally.
[0003] In these techniques, connections between stacked chips are required. Through Silicon Via (TSV) technology is increasingly being adopted for such connections. TSV technology is a technology in which electrodes are provided that penetrate silicon semiconductor chips in the thickness direction, and the connections between stacked chips are made through these electrodes.
[0004] In the manufacture of electronic components including such stacked chips, a process has been used in which, after each chip is stacked, sealing is performed between the wafer and the chip or between the chips themselves, and then the entire stacked chips are covered with a liquid curable resin composition and subjected to compression molding together with the chips to form the external shape of the electronic component (overmolding). However, in recent years, in order to improve manufacturing efficiency, a technique has been increasingly used in which, after all chips are stacked without sealing, the entire stacked chips are covered with a liquid curable resin composition and subjected to compression molding together with the chips, thereby sealing between the wafer and the chips and between each chip, and forming the external shape of the electronic component in one step. In such a technique, the wafer level chip size packaging technique (which involves sealing a wafer that has not been cut into chips after the completion of circuit formation) is often used. The curable resin composition used in such a technique is called a molded underfill material for TSVs or a molded underfill composition for TSVs. Liquid epoxy resin compositions are mainly used as molded underfill materials for TSVs. In this specification, an electronic component that contains a chip (a type of semiconductor element) in a sealed state and is manufactured by the above-mentioned technique is referred to as a "semiconductor package."
[0005] Such molded underfill materials often contain a filler and / or a colorant. The former is added mainly for the purpose of reducing the thermal expansion coefficient and improving the strength of the cured product of the molded underfill material. Silica filler is usually used as this filler. The latter is added to reduce the effect of light on the wiring in electronic components, but the former may be added in combination with the latter to support the function of the latter. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Patent application 2022-010900 [Patent Document 2] JP 2021-172793 A [Patent Document 3] International Publication No. 2019 / 131670 [Patent Document 4] JP 2017-179185 A Summary of the Invention [Problem to be solved by the invention]
[0007] As described above, semiconductor devices including electronic components including multiple chips stacked three-dimensionally with high-density wiring have a problem in that their performance is degraded by heat generated when the electronic components are operated. This problem is caused by the fact that the high-density wiring makes it difficult to dissipate the generated heat because the distance between the chip and the wafer or between the chips is short. This problem is even more serious in semiconductor devices including electronic components manufactured using a mold underfill material containing silica filler with low thermal conductivity.
[0008] In addition, in a semiconductor device including electronic components having a plurality of bumps with high-density wiring as described above, there is a possibility that short circuits may occur between the bumps, and there is a problem in reliability. As the distance between the bumps becomes shorter due to high-density wiring, this problem is becoming more apparent. Such short circuits are likely to occur when the content of ionic impurities, particularly chloride ions, is high in the curable resin composition (e.g., mold underfill material for TSV) used in the manufacture of the electronic components.
[0009] There are various types of reliability tests for electronic components, one of which is the high-rate accelerated life test (HAST test), which is a reliability test conducted under high temperature and high humidity conditions (e.g., 130°C and 85% relative humidity) that accelerate the corrosion of the inside of the electronic component (especially the metal parts). There are two types of HAST tests: one in which no bias voltage is applied to the electronic component being tested (non-bias HAST test), and one in which a bias voltage is applied (bias HAST test). When electronic components manufactured using a conventional liquid epoxy resin composition as a mold underfill material for TSVs are subjected to a reliability test, particularly a bias HAST test, they are prone to short-circuiting in a short time.
[0010] In order to solve the above-mentioned problems of the conventional technology, the present invention aims to provide a liquid epoxy resin composition suitable for use as a mold underfill material for TSV, which can provide electronic components that contain high-density wiring but can sufficiently dissipate heat generated during operation and have high reliability. [Means for solving the problem]
[0011] The present inventors have conducted extensive research to solve the above problems and have arrived at the present invention.
[0012] That is, the present invention includes, but is not limited to, the following inventions.
[0013] A liquid epoxy resin composition for use as a mold underfill material for TSV, comprising the following (A) to (D): (A) epoxy resin; (B) a hardener; (C) an inorganic filler consisting of a silica filler and an alumina filler; and (D) Carbon black Including, The (A) epoxy resin is represented by the following formula (I): [ka] [In the formula, n is an integer of 1 to 15.] The epoxy resin includes an aliphatic epoxy resin represented by The average particle size of the alumina filler is 0.1 μm to 0.3 μm, the content of the (D) carbon black is 0.1 parts by mass or more and 1.5 parts by mass or less when the mass of the (A) epoxy resin is 100 parts by mass, A liquid epoxy resin composition which gives a cured product having a thermal conductivity of 0.8 W / m·K or more and less than 1.2 W / m·K.
[0014] (E) further comprising an ion trapping agent; Chloride ion (Cl - ) is 0.01 ppm or more and less than 2.5 ppm based on the total mass of the liquid epoxy resin composition, The content of the chloride ions is 0.1 g / cm when the cured product of the liquid epoxy resin composition is crushed into 5 mm squares. 3 2. The liquid epoxy resin composition according to item 1, wherein the viscosity of the liquid epoxy resin composition is measured by a method comprising: immersing the composition in water for 20 hours under conditions of a temperature of 121°C, a humidity of 100% and 2 atm, and subjecting the extract obtained to ion chromatography.
[0015] 3. The liquid epoxy resin composition according to item 2 above, wherein the (E) ion trapping agent comprises at least one selected from the group consisting of bismuth-based compounds, zirconium-based compounds, and antimony-based compounds.
[0016] 3. The liquid epoxy resin composition according to item 2 above, wherein the average particle size of the ion trapping agent (E) is 0.01 μm to 2 μm.
[0017] The total chlorine content of the aliphatic epoxy resin represented by formula (I) is 3000 ppm or less, 2. The liquid epoxy resin composition according to item 1 above, wherein the (A) epoxy resin contains, in combination with the aliphatic epoxy resin represented by formula (I), another epoxy resin having a total chlorine content of 3000 ppm or less.
[0018] 2. The liquid epoxy resin composition according to item 1 above, wherein the content of the inorganic filler (C) is 50 to 90 parts by mass when the total mass of the liquid epoxy resin composition is 100 parts by mass.
[0019] 2. The liquid epoxy resin composition according to item 1 above, wherein the (A) epoxy resin further contains an epoxy resin having an aromatic ring in the molecule.
[0020] 2. The liquid epoxy resin composition according to item 1 above, wherein the (B) curing agent comprises at least one selected from the group consisting of phenolic compounds and nitrogen-containing heterocyclic compounds.
[0021] 2. The liquid epoxy resin composition according to item 1, further comprising (F) a silicone-based additive.
[0022] 2. The liquid epoxy resin composition according to item 1, further comprising (G) a coupling agent.
[0023] 2. The liquid epoxy resin composition according to item 1 above, wherein the content of particles having a particle size of more than 1 μm in the inorganic filler (C) is less than 1.0 part by mass when the total mass of the inorganic filler (C) is 100 parts by mass.
[0024] 2. The liquid epoxy resin composition according to item 1, wherein the alumina filler is surface-treated with a silane coupling agent having a methacryloxy group or a phenylamino group.
[0025] 2. A semiconductor package having a semiconductor element encapsulated with the liquid epoxy resin composition according to item 1. Effect of the Invention
[0026] The liquid epoxy resin composition of the present invention gives a cured product with high thermal conductivity. Therefore, electronic components manufactured using the liquid epoxy resin composition of the present invention as a molded underfill material for TSVs can fully release heat generated during operation even if the distance between the chip and wafer or between the chips is short. In a semiconductor device including such electronic components, performance degradation due to heat is suppressed. In addition, electronic components including a cured product obtained by curing the liquid epoxy resin composition of the present invention do not short circuit for a long period of time in a bias HAST test. Therefore, electronic components manufactured using the liquid epoxy resin composition of the present invention as a molded underfill material for TSVs show sufficient reliability even if the distance between bumps is short. Therefore, the liquid epoxy resin composition of the present invention is extremely suitable for use as a molded underfill material for TSVs. [Brief description of the drawings]
[0027] [Figure 1] 1A to 1C are diagrams showing the procedure of encapsulation and overmolding using a molded underfill material for TSVs. [Diagram 2] 1A and 1B are schematic diagrams showing the positions of a silicon wafer, silicon chip, and spacers used to evaluate the injectability of a mold underfill material for TSVs. (A) is a schematic diagram showing the position of a silicon chip arranged on a silicon wafer. (B) is a schematic diagram showing the positions of a silicon chip and spacers on a silicon wafer. [Diagram 3] 1 is a micrograph showing the results of an evaluation of the injectability of TSV molded underfill material. (A) is a micrograph of the polished surface of a test piece made using a TSV molded underfill material with poor injectability. (B) is a micrograph of the polished surface of a test piece made using a TSV molded underfill material with good injectability. [Figure 4] FIG. 2 is a schematic diagram showing the shape of an interdigital electrode used in a bias HAST test. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0028] Hereinafter, an embodiment of the present invention will be described in detail. The present invention relates to a mold underfill material for TSV, comprising the following (A) to (D): (A) epoxy resin; (B) a hardener; (C) an inorganic filler consisting of a silica filler and an alumina filler; and (D) Carbon black In this composition, the epoxy resin (A) is a liquid epoxy resin having the following formula (I): [ka] [In the formula, n is an integer of 1 to 15.] The alumina filler has an average particle size of 0.1 μm to 0.3 μm. When the mass of the epoxy resin (A) is 100 parts by mass, the content of the carbon black (D) is 0.1 parts by mass or more and 1.5 parts by mass or less. This liquid epoxy resin composition also gives a cured product having a thermal conductivity of 0.8 W / m·K or more and less than 1.2 W / m·K. The components (A) to (D) contained in the liquid epoxy resin composition of the present invention will be described below.
[0029] (A) Epoxy resin The liquid epoxy resin composition of the present invention contains an epoxy resin. It is preferable to use an epoxy resin that is liquid at room temperature. It is also preferable to use a liquid epoxy resin having a viscosity in the range of 10 to 5000 mPa·s. By using a liquid epoxy resin, it is possible to obtain a liquid epoxy resin composition that has low viscosity and excellent flowability and is suitable for use as a mold underfill material for TSV. In the liquid epoxy resin composition of the present invention, the content of the epoxy resin is preferably 10 to 35 parts by mass, more preferably 12 to 32 parts by mass, and particularly preferably 15 to 30 parts by mass, when the total mass of the liquid epoxy resin composition is 100 parts by mass. By setting the content within this range, it is possible to suppress an increase in the viscosity of the liquid epoxy resin composition and to reduce the thermal expansion coefficient of the cured product of the liquid epoxy resin composition. The epoxy resin has the following formula (I): [ka] [In the formula, n is an integer of 1 to 15.] The aliphatic epoxy resin (diglycidyl ether of (poly)tetramethylene glycol) represented by the formula: n in this aliphatic epoxy resin can be calculated from the molecular weight of the epoxy resin (number average molecular weight converted into standard polystyrene by gel permeation chromatography (GPC) using tetrahydrofuran as an elution solvent). By including this aliphatic epoxy resin, it is possible to suppress the occurrence of warpage after the liquid epoxy resin composition applied to a wafer on which a semiconductor chip is mounted is cured.
[0030] As the aliphatic epoxy resin represented by the formula (I), commercially available products such as trade name "YX7400N" (manufactured by Mitsubishi Chemical Corporation) and trade name "Epogose PT (general grade)" (manufactured by Yokkaichi Synthetic Co., Ltd.) may be used.
[0031] In the liquid epoxy resin composition of the present invention, the epoxy resin may contain other epoxy resins in addition to the aliphatic epoxy resin represented by the formula (I). As the other epoxy resin, an epoxy resin used as a sealing material can be used. This epoxy resin is preferably a multifunctional epoxy resin having two or more functionalities. Examples of multifunctional epoxy resins include: Monocyclic aromatic epoxy resins such as catechol diglycidyl ether, resorcinol diglycidyl ether, phthalic acid diglycidyl ester, 2,5-diisopropylhydroquinone diglycidyl ether, and hydroquinone diglycidyl ether; alicyclic epoxy resins such as 3',4'-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate, 3,4-epoxy-6-methylcyclohexylmethyl-3,4-epoxy-6-methylcyclohexylcarboxylate, bis(3,4-epoxycyclohexyl)adipate, vinylcyclohexene monoepoxide, and diepoxylimonene; Bisphenol type epoxy resins such as bisphenol A type, bisphenol F type, bisphenol AD type, bisphenol S type, etc.; A mixture of oligomers obtained by partial polymerization of bisphenol-type epoxy resins; Ring-hydrogenated bisphenol-type epoxy resins; Tetramethylbis(4-hydroxyphenyl)methane diglycidyl ether;Tetramethylbis(4-hydroxyphenyl)ether diglycidyl ether; Fluorene-type epoxy resins such as bisphenol fluorene-type epoxy resins and biscresol fluorene-type epoxy resins; Naphthalene type epoxy resin etc. can be mentioned.
[0032] Further, examples of polyfunctional epoxy resins include: Polyfunctional glycidylamine type epoxy resins, such as aminophenol type epoxy resins such as triglycidyl-p-aminophenol, aniline type epoxy resins such as diglycidylaniline, toluidine type epoxy resins such as diglycidylorthotoluidine, and diaminodiphenylmethane type epoxy resins such as tetraglycidyldiaminodiphenylmethane; Dicyclopentadiene type epoxy resin; Polyfunctional glycidyl ethers such as trimethylolalkane type epoxy resins, such as trimethylolpropane triglycidyl ether, trimethylolmethane triglycidyl ether, and trimethylolethane triglycidyl ether Examples include:
[0033] Other epoxy resins, such as aliphatic epoxy resins, silylated epoxy resins, heterocyclic epoxy resins, diallyl bisphenol A type epoxy resins, polyarylene ether diglycidyl ethers, etc., can also be used in combination. In the liquid epoxy resin composition of the present invention, these epoxy resins may be used alone or in combination of two or more kinds.
[0034] The other epoxy resin is preferably an epoxy resin having an aromatic ring in the molecule. In one embodiment of the present invention, the epoxy resin (A) further contains an epoxy resin having an aromatic ring in the molecule in addition to the aliphatic epoxy resin represented by the formula (I). By using an epoxy resin having an aromatic ring in the molecule, the curability of the liquid epoxy resin composition is improved, and the heat resistance is improved, resulting in good bias HAST test results. The mass ratio of the aliphatic epoxy resin represented by the formula (I) to the epoxy resin having an aromatic ring is preferably 5:95 to 50:50, more preferably 10:90 to 45:55, and particularly preferably 20:80 to 40:60. By setting the mass ratio within this range, the occurrence of warpage after the liquid epoxy resin composition applied to a wafer on which a semiconductor chip is mounted is cured can be suppressed, and good bias HAST test results can be obtained. As the epoxy compound having an aromatic ring in the molecule, any known or commonly used aromatic epoxy compound can be used without any particular limitation. Specific examples of epoxy compounds having an aromatic ring in the molecule include: Glycidyl ethers of phenols such as bisphenol A, bisphenol F, bisphenol AD, bisphenol S, catechol, and resorcinol: Glycidyl ether esters of hydroxycarboxylic acids such as p-hydroxybenzoic acid; Mono- or polyglycidyl esters of carboxylic acids such as benzoic acid, phthalic acid, terephthalic acid, etc.; glycidylamine-type epoxy compounds such as diglycidylaniline, diglycidyltoluidine, triglycidyl-p-aminophenol, and tetraglycidyl-m-xylylenediamine; Epoxy compounds with a naphthalene skeleton, such as glycidyl esters of naphthol, glycidyl ether esters of β-hydroxynaphthoic acid, etc. Among these, glycidylamine type epoxy compounds are preferred. In the present invention, so long as the liquid epoxy resin composition of the present invention is liquid at room temperature, the epoxy resin (A) may contain an epoxy resin that is solid at room temperature, such as a biphenyl type epoxy resin and / or a novolac type epoxy resin (including analogs thereof).
[0035] As will be described later, from the viewpoint of reliability, the chloride ion (Cl - ) is preferably low. Therefore, the chloride ion content in the epoxy resin contained in the (A) epoxy resin is also preferably low. The total chlorine content of each epoxy resin contained in the (A) epoxy resin is preferably 3000 ppm or less, more preferably 2500 ppm or less, and particularly preferably 1500 ppm or less. This applies to both the aliphatic epoxy resin represented by formula (I) and other epoxy resins. In one embodiment, the total chlorine content of the aliphatic epoxy resin represented by formula (I) is 3000 ppm or less, and the (A) epoxy resin contains, in combination with the aliphatic epoxy resin represented by formula (I), other epoxy resins having a total chlorine content of 3000 ppm or less.
[0036] (B) Hardener The liquid epoxy resin composition of the present invention contains a curing agent. The curing agent is not particularly limited as long as it can cure the epoxy resin (A). Examples of curing agents that can be used in the liquid epoxy resin composition of the present invention include phenol compounds, acid anhydrides, amine compounds (particularly non-cyclic amine compounds), nitrogen-containing heterocyclic compounds (particularly imidazole compounds), and organometallic compounds. In some embodiments, basic compounds are used among these.
[0037] As an example of the phenolic compound, a phenolic resin, particularly a novolac resin obtained by condensing a phenol or naphthol (e.g., phenol, cresol, naphthol, alkylphenol, bisphenol, terpene phenol, etc.) with formaldehyde is preferably used. Examples of novolac resins include phenol novolac resin, o-cresol novolac resin, p-cresol novolac resin, α-naphthol novolac resin, β-naphthol novolac resin, t-butylphenol novolac resin, bisphenol A type novolac resin, xylylene modified novolac resin, decalin modified novolac resin, etc. Examples of other phenolic resins include dicyclopentadiene cresol resin, polyparavinylphenol, poly(di-o-hydroxyphenyl)methane, poly(di-m-hydroxyphenyl)methane, and poly(di-p-hydroxyphenyl)methane, etc.
[0038] Examples of the acid anhydride include phthalic anhydride, hexahydrophthalic anhydride, alkyl hexahydrophthalic anhydrides such as methyl hexahydrophthalic anhydride, tetrahydrophthalic anhydride, alkyl tetrahydrophthalic anhydrides such as trialkyl tetrahydrophthalic anhydride and 3-methyl tetrahydrophthalic anhydride, himic anhydride, succinic anhydride, trimellitic anhydride, pyromellitic anhydride, etc. Among these, methyl tetrahydrophthalic anhydride, methyl hexahydrophthalic anhydride, etc. are preferred.
[0039] Examples of the (non-cyclic) amine compound include 2,4,6-tris(dimethylaminomethyl)phenol, diethylamine, triethylamine, diethylenetetramine, triethylenetetramine, tetramethyldiaminodiphenylmethane, tetraethyldiaminodiphenylmethane, diethyldimethyldiaminodiphenylmethane, dimethyldiaminotoluene, diaminodibutyltoluene, diaminodipropyltoluene, diaminodiphenylsulfone, diaminoditolylsulfone, diethyldiaminotoluene, bis(4-amino-3-ethylphenyl)methane, polytetramethylene oxide-di-p-aminobenzoate, and 4,4-dimethylaminopyridine. The amine compound may be an amine adduct.
[0040] Examples of the nitrogen-containing heterocyclic compounds include imidazoles such as 2-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 2,4-diamino-6-[2'-methylimidazolyl-(1')]ethyl-s-triazine, 2-phenyl-4,5-dihydroxymethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, and 2,3-dihydro-1H-pyrrolo[1,2-a]benzimidazole; Examples of the nitrogen-containing heterocyclic compound include diazabicyclononene (DBU), DBU-phenol salt, DBU-octylate salt, DBU-p-toluenesulfonate, DBU-formate, DBU-orthophthalate, DBU-phenol novolac resin salt, DBU-based tetraphenylborate salt, diazabicyclononene (DBN), DBN-phenol novolac resin salt, diazabicyclooctane, pyrazole, oxazole, thiazole, imidazoline, pyrazine, morpholine, thiazine, indole, isoindole, benzimidazole, purine, quinoline, isoquinoline, quinoxaline, cinnoline, and pteridine. The nitrogen-containing heterocyclic compound may be one that forms an adduct with an epoxy resin or an isocyanate compound, or one that is microencapsulated.
[0041] Examples of the organometallic compound include zinc naphthenate, cobalt naphthenate, tin octoate, cobalt octoate, bis(acetylacetonate)cobalt(II), and tris(acetylacetonate)cobalt(III).
[0042] In the present invention, the curing agent preferably contains at least one selected from the group consisting of phenolic compounds, acid anhydrides, non-cyclic amine compounds and nitrogen-containing heterocyclic compounds, more preferably contains at least one selected from the group consisting of phenolic compounds and nitrogen-containing heterocyclic compounds, and further preferably contains a nitrogen-containing heterocyclic compound. The nitrogen-containing heterocyclic compound may be latent, and a microcapsule-type latent curing agent may also be used. The nitrogen-containing heterocyclic compound is particularly preferably an imidazole compound. Examples of the imidazole compound include 2-substituted imidazole compounds such as imidazole, 2-methylimidazole, 2-ethylimidazole, 1-isobutyl 2-methylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, 1-benzyl-2-phenylimidazole, 1,2-dimethylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-undecylimidazole, and 1-cyanoethyl-2-phenylimidazole; trimer compounds such as 1-cyanoethyl-2-undecylimidazolium trimellitate and 1-cyanoethyl-2-phenylimidazolium trimellitate; triazine compounds such as 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-undecylimidazolyl-(1')]-ethyl-s-triazine, and 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine; an isocyanuric acid adduct of 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine, an isocyanuric acid adduct of 2-phenylimidazole, an isocyanuric acid adduct of 2-methylimidazole, an isocyanuric acid adduct of 2-phenyl-4,5-dihydroxymethylimidazole, and an isocyanuric acid adduct of 2-phenyl-4-methyl-5-dihydroxymethylimidazole.
[0043] As the microcapsule type curing agent, for example, a dispersion liquid in which a powder of an amine compound (including a nitrogen-containing heterocyclic compound) is dispersed in a liquid epoxy resin can be used. The amine compound may be selected from, for example, an aliphatic primary amine, an alicyclic primary amine, an aromatic primary amine, an aliphatic secondary amine, an alicyclic secondary amine, an aromatic secondary amine, an imidazole compound, and an imidazoline compound. The amine compound may be used in the form of a reaction product with a carboxylic acid, a sulfonic acid, an isocyanate, an epoxide, or the like. These compounds may be used alone or in combination of two or more. For example, the amine compound may be used in combination with its reaction product with a carboxylic acid, a sulfonic acid, an isocyanate, or an epoxide. The volume average particle size of the powder of the amine compound is preferably 50 μm or less, more preferably 10 μm or less. In addition, it is preferable that the powder of the amine compound has a melting point or softening point of 60° C. or more in terms of suppressing viscosity increase at 25° C.
[0044] In the liquid epoxy resin composition of the present invention, the curing agent may be used alone or in combination of two or more. In the present invention, the curing agent is preferably an imidazole compound, and more preferably an imidazole compound and a phenol compound are used in combination. By using an imidazole compound and a phenol compound in combination, it is possible to improve the curability while improving the storage stability.
[0045] In the liquid epoxy resin composition of the present invention, the content of the curing agent is preferably 1 to 20 mass % relative to the epoxy resin (A), more preferably 2 to 17 mass %, and particularly preferably 3 to 15 mass %. By setting the content within this range, the curing time of the liquid epoxy resin composition is not too long, the productivity of electronic components including high-density wiring formed by techniques such as TSV is improved, the occurrence of warpage after the liquid epoxy resin composition applied to a wafer mounted with a semiconductor chip is cured is suppressed, and the storage stability of the liquid epoxy resin composition is improved.
[0046] (C) Inorganic filler The liquid epoxy resin composition of the present invention contains an inorganic filler. The inorganic filler comprises a silica filler and an alumina filler. The liquid epoxy resin composition of the present invention, which contains an alumina filler having high thermal conductivity, gives a cured product having high thermal conductivity. Therefore, in electronic components manufactured using the liquid epoxy resin composition of the present invention as a mold underfill material for TSV, heat generated during operation is easily released. This contributes to further improving the performance of electronic devices.
[0047] The alumina filler includes alumina powder. The alumina powder is available as a commercial product. The shape of the alumina filler particles is not particularly limited, and may be any shape, such as spherical, irregular, or flaky. From the viewpoint of the fluidity of the liquid epoxy resin composition when used as a mold underfill material for TSV, it is particularly preferable that the alumina filler particles are spherical. Such an alumina filler can be highly filled, and is therefore also preferable from the viewpoint of improving the thermal conductivity of the cured product. The alumina filler may be surface-treated with a surface treatment agent, for example, a silane coupling agent (which may have a substituent such as a phenyl group, a vinyl group, or a methacryloyl group). By using a surface-treated alumina filler, the viscosity of the liquid epoxy resin composition can be reduced, and the injectability can be improved. "Injectability" refers to the degree of ease of filling the liquid epoxy resin composition between the chip and wafer or between the chips during compression molding. From the viewpoint of injection property when the liquid epoxy resin composition is applied as a mold underfill material for TSV and reduction of warpage of the cured product, it is particularly preferable to use an alumina filler surface-treated with a silane coupling agent containing a methacryloxy group or a phenylamino group. In one embodiment, the alumina filler is surface-treated with a silane coupling agent containing a methacryloxy group or a phenylamino group. Any of such surface-treated alumina fillers improves the above-mentioned properties of the liquid epoxy resin composition. However, the above-mentioned properties are usually improved when an alumina filler surface-treated with a silane coupling agent containing a methacryloxy group is used compared to when an alumina filler surface-treated with a silane coupling agent containing a phenylamino group is used. In one embodiment, the alumina filler is surface-treated with a silane coupling agent containing a methacryloxy group.
[0048] The average particle size of the alumina filler used in the present invention is 0.1 μm to 0.3 μm, preferably 0.15 μm to 0.25 μm. If the average particle size of the alumina filler is less than 0.1 μm, the viscosity of the liquid epoxy resin composition is likely to be high. Therefore, it becomes difficult to add an amount of alumina filler required for sufficiently improving the thermal conductivity to the liquid epoxy resin composition. On the other hand, if the average particle size of the alumina filler is more than 0.3 μm, the injectability of the liquid epoxy resin composition decreases. The average particle size of the alumina filler is the particle size at 50% of the cumulative volume of the volume particle size distribution (D 50 More specifically, samples are randomly extracted from the population, and the particle size distribution is measured using a laser diffraction / scattering particle size analyzer, and the average particle size, etc. can be calculated based on this particle size distribution.
[0049] It has been known for some time that alumina filler is added to sealing materials used in the manufacture of electronic components for the purpose of improving thermal conductivity, etc. (See Patent Documents 2 and 3). However, the usefulness of adding alumina filler to a liquid epoxy resin composition used as a mold underfill material for TSVs, and the properties of alumina filler suitable for this application were discovered for the first time by the present inventors.
[0050] In the liquid epoxy resin composition of the present invention, the content of the alumina filler is preferably 40 to 80 parts by mass, more preferably 45 to 78 parts by mass, and particularly preferably 50 to 75 parts by mass, relative to 100 parts by mass of the total mass of the liquid epoxy resin composition.
[0051] Furthermore, the liquid epoxy resin composition of the present invention, which contains a silica filler in addition to an alumina filler, gives a cured product having a reduced coefficient of linear thermal expansion. The silica filler includes silica powder. The silica powder can be obtained as a commercial product. The silica may be natural silica (silica stone, quartz, etc.) or synthetic silica. The synthetic silica can be synthesized by any method including a dry method and a wet method.
[0052] Preferably, fused silica powder is used as the silica filler. Examples of the fused silica powder include spherical fused silica powder and crushed fused silica powder, but from the viewpoint of the fluidity of the liquid epoxy resin composition, it is more preferable to use spherical fused silica powder (particularly, one consisting of particles with high sphericity) as the silica filler.
[0053] The silica filler may be surface-treated with a surface treatment agent, for example, a silane coupling agent (which may have a substituent such as an epoxy group, an amino group, a phenyl group, a vinyl group, or a (meth)acryloyl group). By using the surface-treated silica filler, the viscosity of the liquid epoxy resin composition can be reduced, and the injectability can be improved.
[0054] The average particle size of the silica filler used in the present invention is preferably 5 nm to 100 nm, more preferably 10 nm to 50 nm. If the average particle size of the silica filler is not within the range of 5 nm to 100 nm, the liquid epoxy resin composition may exhibit inappropriate viscosity and / or injectability. The average particle size of the silica filler can be obtained by analyzing a micrograph (e.g., an electron microscope photograph) taken of a sample of component (C) using image processing software, and quantifying and statistically processing the sizes of all or part of the particles in the micrograph.
[0055] In the liquid epoxy resin composition of the present invention, the content of the silica filler is preferably 5 to 23 parts by mass, and more preferably 8 to 19 parts by mass, relative to 100 parts by mass of the total mass of the liquid epoxy resin composition.
[0056] The inorganic filler (C) used in the present invention is composed of a silica filler and an alumina filler, and does not contain other fillers. If the inorganic filler (C) contains other fillers, it is not preferable because the liquid epoxy resin composition cannot be highly filled with the fillers, and the thermal conductivity and fluidity are reduced. This is because the sphericity of the other fillers is lower than that of the silica filler and the alumina filler.
[0057] In the liquid epoxy resin composition of the present invention, the content of the (C) inorganic filler is preferably 50 to 90 parts by mass, more preferably 55 to 88 parts by mass, and particularly preferably 60 to 85 parts by mass, relative to 100 parts by mass of the total mass of the liquid epoxy resin composition. The mass ratio of the silica filler to the alumina filler is preferably from 40:60 to 1:99, more preferably from 30:70 to 5:95, and particularly preferably from 20:80 to 10:90.
[0058] By adding the inorganic filler (C) as described above, the liquid epoxy resin composition of the present invention provides a cured product with improved thermal conductivity. Specifically, the liquid epoxy resin composition of the present invention provides a cured product with a thermal conductivity of 0.8 W / m·K or more and less than 1.2 W / m·K. If the thermal conductivity of the cured product provided by the liquid epoxy resin composition of the present invention is less than 0.8 W / m·K, the heat generated during operation of an electronic component containing the cured product is not sufficiently released. The thermal conductivity of the cured product is preferably 0.7 W / m·K or more, more preferably 0.75 W / m·K or more, and particularly preferably 0.8 W / m·K or more. On the other hand, although the thermal conductivity of the cured product is improved by the alumina filler, it is less than 1.2 W / m·K due to the coexistence of other components. In addition, the cured product obtained from the liquid epoxy resin composition of the present invention has a reduced coefficient of linear thermal expansion due to the addition of the inorganic filler (C).
[0059] In electronic components including multiple chips stacked three-dimensionally, the distance between the chip and the wafer and between the chips is becoming shorter as the wiring density increases. In such electronic components, the heat generated during operation is difficult to dissipate, and the performance of the semiconductor device including such electronic components may be reduced due to the heat. Dissipation of this heat becomes more difficult in semiconductor devices including electronic components manufactured using a mold underfill material containing silica filler with low thermal conductivity. On the other hand, the thermal conductivity of the cured product obtained by the liquid epoxy resin composition of the present invention is higher than that of the cured product obtained by the conventional molded underfill material for TSV. Therefore, electronic components manufactured by using the liquid epoxy resin composition of the present invention as a molded underfill material for TSV can sufficiently dissipate heat generated during operation even if the distance between the chip and the wafer or between the chips is short. In semiconductor devices including such electronic components, the performance degradation due to heat is suppressed.
[0060] In the present invention, from the viewpoint of injectability, it is particularly preferred that the content of particles having a particle size of more than 1 μm in the inorganic filler (C) is less than 1.0 part by mass when the total mass of the inorganic filler (C) is taken as 100 parts by mass. The liquid epoxy resin composition of the present invention may further contain, as an optional component, a silica filler and / or an alumina filler having an average particle size of less than 0.1 μm, within a range that does not adversely affect the properties of the composition.
[0061] (D) Carbon black The liquid epoxy resin composition of the present invention contains carbon black. Considering the possibility that wiring in electronic components may be affected by light, the use of carbon black is important. The carbon black is not particularly limited, and any carbon black that is usually used as the carbon black contained in an epoxy resin composition can be appropriately selected and used. Examples of such carbon black include acetylene black, furnace black, ketjen black, channel black, lamp black, and thermal black. These may be used alone or in combination of two or more.
[0062] In the present invention, carbon black may be used in combination with other black pigments. As the other black pigments, black organic pigments, mixed color organic pigments, black inorganic pigments, etc. can be used. Examples of black organic pigments include perylene black, aniline black, etc. Examples of mixed color organic pigments include those that are pseudo-blackened by mixing at least two or more pigments selected from red, blue, green, purple, yellow, magenta, cyan, etc. Examples of black inorganic pigments include graphite, and fine particles of metals and their oxides (including complex oxides), sulfides, nitrides, etc. Examples of the metals include titanium, copper, iron, manganese, cobalt, chromium, nickel, zinc, calcium, silver, etc. Carbon black may also be used in combination with other colorants, such as dyes.
[0063] In the liquid epoxy resin composition of the present invention, the content of carbon black is 0.1 parts by mass or more and 1.5 parts by mass or less, when the mass of the epoxy resin (A) is 100 parts by mass. The content of carbon black is preferably 0.1 parts by mass or more and 1.3 parts by mass or less, more preferably 0.1 parts by mass or more and 1.1 parts by mass or less. Furthermore, the content of carbon black is preferably 0.01 parts by mass or more and 0.60 parts by mass or less, more preferably 0.01 parts by mass or more and 0.45 parts by mass or less, and even more preferably 0.01 parts by mass or more and 0.30 parts by mass or less, when the total mass of the liquid epoxy resin composition is 100 parts by mass. If the carbon black content is less than the above range, the light shielding is insufficient, and the wiring in the electronic component may be affected by light. If the carbon black content exceeds the above range, the electronic component obtained by packaging multiple chips stacked using the TSV technology with the liquid epoxy resin composition is likely to short circuit in the bias HAST test. In other words, the reliability of such electronic components is reduced.
[0064] If desired, the liquid epoxy resin composition of the present invention may contain optional components such as those described below, in addition to the above-mentioned components (A) to (D) which are essential components.
[0065] (E) Ion trapping agent The liquid epoxy resin composition of the present invention may contain an ion trapping agent, if desired. In one embodiment, the liquid epoxy resin composition of the present invention further contains an ion trapping agent. The ion trapping agent is a compound that captures ion impurities contained in a resin such as (A) epoxy resin. By including an ion trapping agent, chloride ions (Cl - ) and other anionic impurities, thereby suppressing short circuits during operation.
[0066] There are ion trapping agents that trap cations and anions, but the ion trapping agent used in the present invention is not particularly limited as long as it can trap chloride ions, and both inorganic and organic compounds can be used. Examples of organic compounds used as ion trapping agents include triazole compounds, tetrazole compounds, and bipyridyl compounds. Examples of inorganic compounds used as ion trapping agents include rare earth oxides, bismuth compounds such as bismuth hydroxide compounds, antimony compounds, titanium compounds, zirconium compounds such as zirconium phosphate having a specific structure, magnesium compounds such as hydrotalcites, and aluminum compounds. From the viewpoint of a higher chloride ion trapping effect, it is preferable to include at least one selected from bismuth compounds, zirconium compounds, and antimony compounds, and it is more preferable to consist of only these compounds. The ion trapping agent may be used alone or in combination of two or more types.
[0067] In the liquid epoxy resin composition of the present invention, the content of the ion trapping agent is preferably 0.5 to 6 parts by mass, more preferably 0.7 to 5 parts by mass, and particularly preferably 1 to 4 parts by mass, based on 100 parts by mass of the epoxy resin (A). By setting the content within this range, the chloride ion concentration in the liquid epoxy resin composition is sufficiently reduced without impairing other properties required as a mold underfill material for TSV. If the content of the ion trapping agent is less than 0.5 parts by mass, chloride ions cannot be effectively trapped, and there is a possibility of short circuiting in the bias HAST test.
[0068] The average particle size of the ion trapping agent used in the present invention is preferably 0.01 μm (10 nm) to 2 μm, more preferably 0.1 μm to 2.0 μm, and further preferably 0.2 μm to 1.5 μm. The average particle size of the ion trapping agent can be determined in the same manner as the average particle size of alumina.
[0069] The upper limit of the average particle size of the ion trapping agent is preferably 2.0 μm, more preferably 1.8 μm, more preferably 1.5 μm, more preferably 1.2 μm, more preferably 1.0 μm, more preferably 0.8 μm, more preferably 0.5 μm, and particularly preferably 0.4 μm, in consideration of the distance between chips and wafers and / or between chips in an electronic component including a plurality of chips stacked three-dimensionally, and the distance between bumps in an electronic component including a plurality of bumps. The lower limit of the average particle size of the ion trapping agent is not limited as long as a liquid epoxy resin composition having appropriate handleability and capable of being injected into narrow passages in electronic components is obtained, but is preferably 0.01 μm (10 nm), more preferably 0.1 μm, and more preferably 0.2 μm.
[0070] As the ion trapping agent, commercially available products can be used, such as the IXE series and IXEPLAS series manufactured by Toagosei Co., Ltd.
[0071] It has been known for some time that an ion trapping agent is added to a sealing material for manufacturing electronic components (see Patent Documents 1 and 4). However, the usefulness of adding an ion trapping agent to a liquid epoxy resin composition used as a mold underfill material for TSVs, and the properties of the ion trapping agent suitable for this application were discovered for the first time by the present inventors.
[0072] (F) Silicone additives The liquid epoxy resin composition of the present invention may contain a silicone-based additive if desired. In one embodiment, the liquid epoxy resin composition of the present invention further contains a silicone-based additive. The inclusion of a silicone-based additive is preferable from the viewpoint of improving the fluidity of the liquid epoxy resin composition. The silicone-based additive is preferably a dialkyl polysiloxane (alkyl groups bonded to Si include methyl, ethyl, etc.), particularly dimethyl polysiloxane. The silicone-based additive may also be a modified dialkyl polysiloxane, for example, an epoxy-modified dimethyl polysiloxane. Specific examples of the silicone-based additive include KF69 (dimethyl silicone oil, manufactured by Shin-Etsu Silicone), SF8421 (epoxy-modified silicone oil, manufactured by Toray Dow Silicone), and the like. The silicone-based additive may be used alone or in combination of two or more kinds.
[0073] When the liquid epoxy resin composition of the present invention contains a silicone-based additive, the amount of the silicone-based additive is preferably 0.1 to 1.0 part by mass, and more preferably 0.25 to 1 part by mass, per 100 parts by mass of the epoxy resin (A).
[0074] (G) Coupling Agent The liquid epoxy resin composition of the present invention may contain a coupling agent if desired. In one embodiment, the liquid epoxy resin composition of the present invention further contains a coupling agent. The inclusion of a coupling agent, particularly a silane coupling agent, is preferred from the viewpoint of improving adhesive strength. As the coupling agent, various silane coupling agents such as epoxy-based, amino-based, vinyl-based, methacryl-based, acrylic-based, and mercapto-based agents can be used. Specific examples of silane coupling agents include 3-glycidoxypropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, vinyltrimethoxysilane, 3-triethoxysilyl-N-(1,3-dimethyl-butylidene)propylamine, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, p-styryltrimethoxysilane, 3-methacryloxypropylmethyltrimethoxysilane, 3-acryloxypropyltrimethoxysilane, 8-glycidoxyoctyltrimethoxysilane, 3-ureidopropyltriethoxysilane, 3-mercaptopropyltrimethoxysilane, bis(triethoxysilylpropyl)tetrasulfide, 3-isocyanatepropyltriethoxysilane, etc. These silane coupling agents may be used alone or in combination of two or more.
[0075] When the liquid epoxy resin composition of the present invention contains a coupling agent, the amount of the coupling agent is preferably 0.01 to 5 parts by mass, and more preferably 0.1 to 3 parts by mass, per 100 parts by mass of the epoxy resin (A).
[0076] (H) Migration inhibitors The liquid epoxy resin composition of the present invention may contain a migration inhibitor if desired. In one embodiment, the liquid epoxy resin composition of the present invention further contains a migration inhibitor. Migration is a phenomenon in which metal in a wiring pattern is eluted by an electrochemical reaction, resulting in a decrease in resistance value. The inclusion of a migration inhibitor is preferable from the viewpoint of improving the reliability of electronic components. Specific examples of the migration inhibitor include xanthines such as caffeine, theophylline, theobromine, and paraxanthine; tocols such as 5,7,8-trimethyltocoi (α-tocopherol), 5,8-dimethyltocoi (β-tocoi), 7,8-dimethyltocoi (γ-tocoi), and 8-methyltocoi (δ-tocoi), and 5,7,8-trimethyltocoi (α-tocoi), 5,8-dimethyltocoi (β-tocoi), and 7,8-dimethyltocoi (γ-tocoi). Tocotrienols such as 8-methyltocotrienol (δ-tocotrienol), benzotriazoles such as benzotriazole, 1H-benzotriazole-1-methanol, and alkylbenzotriazoles, triazines such as 2,4-diamino-6-vinyl-S-triazine, 2,4-diamino-6-[2'-ethyl-4-methylimidazole-(1)]-ethyl-S-triazine, and 2,4-diamino-6-methacryloyloxyethyl-S-triazine, and isocyanuric acid adducts of the above benzotriazoles or triazines. These migration inhibitors may be used alone or in combination of two or more.
[0077] When the liquid epoxy resin composition of the present invention contains a migration inhibitor, the amount of the migration inhibitor is preferably 0.01 to 5 parts by mass, and more preferably 0.1 to 3 parts by mass, per 100 parts by mass of the epoxy resin (A).
[0078] (I) Stabilizers The liquid epoxy resin composition of the present invention may contain a stabilizer if desired. The stabilizer may be contained in the liquid epoxy resin composition of the present invention in order to improve its storage stability and extend its pot life. Various stabilizers known as stabilizers for one-component adhesives based on epoxy resins can be used, but at least one selected from the group consisting of liquid borate ester compounds, aluminum chelates, and organic acids is preferred because of its high effect of improving storage stability.
[0079] Examples of liquid boric acid ester compounds include 2,2'-oxybis(5,5'-dimethyl-1,3,2-oxaborinane), trimethyl borate, triethyl borate, tri-n-propyl borate, triisopropyl borate, tri-n-butyl borate, tripentyl borate, triallyl borate, trihexyl borate, tricyclohexyl borate, trioctyl borate, trinonyl borate, tridecyl borate, tridodecyl borate, trihexadecyl borate, trioctadecyl borate, tris(2-ethylhexyloxy)borane, bis(1,4,7,10-tetraoxaundecyl)(1,4,7,10,13-pentaoxatetradecyl)(1,4,7-trioxaundecyl)borane, tribenzyl borate, triphenyl borate, tri-o-tolyl borate, tri-m-tolyl borate, and triethanolamine borate. The liquid boric acid ester compound is preferable because it is liquid at room temperature (25°C), and therefore the viscosity of the liquid epoxy resin composition can be kept low. As the aluminum chelate, for example, aluminum chelate A can be used. As the organic acid, for example, barbituric acid can be used.
[0080] When the liquid epoxy resin composition of the present invention contains a stabilizer, the amount of the stabilizer is preferably 0.01 to 30 parts by mass, more preferably 0.05 to 25 parts by mass, and even more preferably 0.1 to 20 parts by mass, relative to 100 parts by mass of the epoxy resin (A).
[0081] (J) Other Additives If desired, the liquid epoxy resin composition of the present invention may contain other additives, such as a leveling agent, an antioxidant, an antifoaming agent, a thixotropic agent, a viscosity modifier, a flame retardant, a reactive diluent, a solvent, an elastomer, etc., within the scope of the present invention. The type and amount of each additive are the same as in the conventional method.
[0082] In the liquid epoxy resin composition of the present invention, one or more of the components (including components (A) to (D)) contained therein may exist as a particulate solid. In the present invention, from the viewpoint of injectability, when the total mass of the liquid epoxy resin composition is 100 parts by mass, the content of particles having a particle size of more than 1 μm is preferably less than 1.0 part by mass.
[0083] The method for producing the liquid epoxy resin composition of the present invention is not particularly limited. For example, the components (A) to (D) and, if desired, the ion trapping agent (E) and other components are introduced simultaneously or separately into an appropriate mixer, and if necessary, are stirred and mixed while melting by heating to obtain a homogeneous composition, thereby obtaining the liquid epoxy resin composition of the present invention. The mixer is not particularly limited, but a Raikai mixer equipped with a stirrer and a heater, a Henschel mixer, a three-roll mill, a ball mill, a planetary mixer, a bead mill, or the like, can be used. These devices may also be used in appropriate combination.
[0084] The liquid epoxy resin composition thus obtained is thermosetting, and at a temperature of 100 to 170° C., it is preferable that it cures in 0.1 to 3 hours, and more preferably in 0.25 to 2 hours.
[0085] In the liquid epoxy resin composition of the present invention, chloride ions (Cl -) is preferably 0.01 ppm or more and less than 7.0 ppm, more preferably 0.01 ppm or more and less than 5.0 ppm, and even more preferably 0.01 ppm or more and less than 3.0 ppm, based on the total mass of the liquid epoxy resin composition. If the chloride ion content is 2.5 ppm or more, an electronic component obtained by packaging a plurality of chips stacked using the TSV technology with the liquid epoxy resin composition is likely to short circuit in the bias HAST test. That is, the reliability of such electronic components is reduced. On the other hand, from the viewpoint of commercial availability, the chloride ion content is preferably 0.01 ppm or more.
[0086] The chloride ion content is measured by subjecting the sample to high heat and pressure (for example, at a concentration of 0.1 g / cm 3 The chloride ion content can be measured by a method comprising extracting the liquid epoxy resin composition of the present invention from the liquid epoxy resin composition at room temperature (under conditions of 121°C, 100% humidity, and 2 atm for 20 hours) with pure water and subjecting the resulting extract to ion chromatography. However, when it is difficult to measure the chloride ion content of the liquid epoxy resin composition of the present invention, this content is deemed to be equal to the chloride ion content of the cured product obtained by curing the liquid epoxy resin composition (pulverized as necessary (for example, into pieces of about 5 mm square)) measured by the above method.
[0087] As described above, in the manufacture of electronic components including stacked chips, a process has been conventionally used in which, after each stack of chips, sealing is performed between the wafer and the chip or between the chips themselves, followed by overmolding. In such a process, a resin composition with a lower chloride ion content than the resin composition used for overmolding is used for sealing.
[0088] In contrast, when using a molded underfill material for TSVs to perform encapsulation and overmolding in one step, the same resin composition must be used for encapsulation and overmolding. Conventional resin compositions for encapsulation are inappropriate as molded underfill materials for TSVs due to reasons such as moisture resistance and resistance to ion elution. On the other hand, when a conventional resin composition for overmolding is used as a molded underfill material for TSVs to manufacture an electronic component including multiple stacked chips, the resulting electronic component is prone to short circuits in bias HAST tests. In other words, such electronic components exhibit low reliability.
[0089] In the liquid epoxy resin composition of the present invention, the content of (D) carbon black is within the above range, and thus the reliability of the electronic component containing the cured product obtained by curing the composition used as a mold underfill material for TSV is improved. However, it is highly preferable that the content of chloride ions in the composition is within the above range, since this reliability is further improved.
[0090] The viscosity of the liquid epoxy resin composition of the present invention, measured using a rotational viscometer at a rotation speed of 20 rpm, at 25°C is preferably 20 Pa·s to 450 Pa·s, more preferably 40 Pa·s to 400 Pa·s, and particularly preferably 60 Pa·s to 350 Pa·s. When the viscosity at 25°C is within this range, the injectability of the liquid epoxy resin composition is improved.
[0091] The thixotropic index (TI) of the liquid epoxy resin composition of the present invention is preferably 0.3 to 5.0, more preferably 0.5 to 4.0, and particularly preferably 1.0 to 3.0. When the TI is within this range, the injectability of the liquid epoxy resin composition is improved. The TI of the liquid epoxy resin composition is expressed by the following formula: TI=η 2 / η 20 (In the formula, η 2is the viscosity of the liquid epoxy resin composition (above) measured using a rotational viscometer at a temperature of 25°C and a rotation speed of 2 rpm, η 20 is η except that the rotation speed is 20 rpm. 2 The viscosity of the liquid epoxy resin composition was measured under the same conditions as in It is expressed as:
[0092] The viscosity of the liquid epoxy resin composition of the present invention at 120°C measured using a rheometer is preferably 1.0 Pa·s to 10 Pa·s, more preferably 1.5 Pa·s to 7 Pa·s, and particularly preferably 2.0 Pa·s to 6 Pa·s. When the viscosity at 25°C is within this range, the injectability of the liquid epoxy resin composition is improved.
[0093] The liquid epoxy resin composition of the present invention can be used as an adhesive, a sealant, or a raw material thereof for fixing, joining, or protecting components constituting a semiconductor device including various electronic components (e.g., semiconductor elements) or components constituting the electronic components. The liquid epoxy resin composition of the present invention is suitable as an underfill material for protecting electronic components and fixing them to a substrate, particularly as a molded underfill material for TSV used in a technique for sealing between a wafer and a chip and between each chip, and for molding the outer shape of an electronic component in one step. As an example of a process for manufacturing electronic components using such a technique, a compression molding process is shown in FIG. 1. A wafer (FIG. 1(A)) on which a plurality of stacked semiconductor chips are mounted is placed in a compression molding device equipped with a mold, and a molded underfill material for TSV is applied to the wafer (FIG. 1(B)). The wafer is subjected to compression molding under heating, and the molded underfill material is then cured by heating (FIG. 1(C)). By such a process, sealing between a wafer on which semiconductor chips are mounted and the chips, and between each chip, as well as molding the outer shape of an electronic component can be achieved in one step.
[0094] The liquid epoxy resin composition of the present invention is particularly useful in the manufacture of electronic components comprising multiple chips stacked in three dimensions and with short chip-to-wafer or chip-to-chip distances, and / or electronic components comprising multiple bumps and with short bump-to-bump distances, using wafer level chip size packaging technology. In an electronic component containing a plurality of chips stacked three-dimensionally, which is produced using the liquid epoxy resin composition of the present invention, the distance between the chip and the wafer and / or between the chips is preferably 40 μm or less, more preferably 30 μm or less, and even more preferably 20 μm or less. In electronic components including a plurality of bumps produced using the liquid epoxy resin composition of the present invention, the average distance between the bumps is preferably 100 μm or less, more preferably 80 μm or less, and even more preferably 40 μm or less.
[0095] The present invention also provides a cured product obtained by curing the liquid epoxy resin composition of the present invention. The present invention further provides an electronic part comprising the cured product of the present invention.
[0096] The present invention also provides a semiconductor element encapsulated with the liquid epoxy resin composition of the present invention. The present invention further provides a semiconductor package having a semiconductor element encapsulated with the liquid epoxy resin composition of the present invention. EXAMPLES
[0097] The present invention will be described below with reference to examples, but the present invention is not limited thereto. In the following description, parts and % refer to parts by mass and % by mass unless otherwise specified.
[0098] Examples 1 to 7, Comparative Example 1, Reference Examples 1 to 4 A liquid epoxy resin composition was prepared by mixing the prescribed amounts of each component using a three-roll mill according to the formulation shown in Table 1. In Table 1, the amount of each component is expressed in parts by mass (unit: g).
[0099] (A) Epoxy resin In the examples, comparative examples and reference examples, the compounds used as the epoxy resin (A) are as follows. (A-1): Aliphatic epoxy resin (product name: YX7400N, manufactured by Mitsubishi Chemical Corporation, total chlorine content 500 ppm, liquid at room temperature) (diglycidyl ether of polytetramethylene glycol) (A-2): Glycidylamine type epoxy resin (product name: jER630LSD, manufactured by Mitsubishi Chemical Corporation, total chlorine content 1500 ppm, liquid at room temperature) (epoxy resin having an aromatic ring) (A-3): Glycidylamine type epoxy resin (product name: jER630, manufactured by Mitsubishi Chemical Corporation, total chlorine content 5000 ppm, liquid at room temperature) (epoxy resin having an aromatic ring)
[0100] (B) Hardener The compounds used as the curing agent (B) in the examples, comparative examples and reference examples are as follows. (B-1): Liquid phenol novolac resin (product name: MEH-8005, manufactured by UBE Corporation) (B-2): 2,4-diamino-6-[2'-methylimidazolyl-(1')]ethyl-s-triazine (product name: Curesol 2MZ-A, manufactured by Shikoku Chemical Industries Co., Ltd.) (B-3): 2-ethyl-4-methylimidazole (product name: Curesol 2E4MZ, manufactured by Shikoku Chemical Industry Co., Ltd.)
[0101] (C) Inorganic filler In the examples, comparative examples and reference examples, the compounds used as the inorganic filler (C) are as follows. (C-1): Alumina filler (product name: AG2030-SMO, manufactured by Admatechs Co., Ltd., average particle size 0.2 μm, maximum particle size 3.0 μm, surface-treated with a silane coupling agent having a methacryloxy group) (C-2): Silica filler (product name: SE101G-SMO, manufactured by Admatechs Co., Ltd., average particle size 0.3 μm, maximum particle size 3.0 μm, surface-treated with a silane coupling agent having a methacryloxy group) (C-3): Silica nanofiller (product name: Admanano YA050C-SM1, manufactured by Admatechs Co., Ltd., average particle size 50 nm, surface-treated with a silane coupling agent having a methacryloxy group)
[0102] (D) Carbon black In the examples, comparative examples and reference examples, the compounds used as carbon black (D) are as follows. (D-1): Carbon black (product name: Special Black 4, manufactured by Orion Engineered Carbons Co., Ltd.) In Table 1, "(D) content" represents the content (parts by mass) of (D) carbon black when the mass of (A) epoxy resin is taken as 100 parts by mass.
[0103] (E) Ion trapping agent In the Examples, Comparative Examples and Reference Examples, the compounds used as the ion trapping agent (E) are as follows. (E-1): Bismuth-based ion trapping agent (product name: IXE-500, manufactured by Toagosei Co., Ltd., average particle size 1.5 μm) (E-2): Zirconium / bismuth-based ion trapping agent (product name: IXEPLAS-B1, manufactured by Toagosei Co., Ltd., average particle size 0.4 μm) (E-3): Zirconium / bismuth-based ion trapping agent (product name: IXE-6136, manufactured by Toagosei Co., Ltd., average particle size 2.1 μm) (E-4): Hydrotalcite-based ion trapping agent (product name: SWMNA-015A-1, manufactured by Toda Kogyo Co., Ltd., average particle size 0.2 μm)
[0104] (F) Silicone additives In the examples, comparative examples and reference examples, the compounds used as the silicone additive (F) are as follows. (F-1): Silicone oil (product name: SF8421, manufactured by Dow Corning Toray Co., Ltd.)
[0105] (G) Coupling Agent The compounds used as coupling agents (G) in the examples, comparative examples and reference examples are as follows. (G-1): 3-glycidoxypropyltrimethoxysilane (product name: KBM403, manufactured by Shin-Etsu Chemical Co., Ltd.)
[0106] In the examples, comparative examples and reference examples, the properties of the liquid epoxy resin compositions and the cured products were measured as follows.
[0107] (Viscosity of liquid epoxy resin composition at 25°C) The viscosity (unit: Pa s) of each of the prepared resin compositions was measured at 25°C and 20 revolutions per minute using a Brookfield HB type rotational viscometer (spindle SC4-14 used). The results are shown in Table 1.
[0108] (Thixotropic Index (TI) of Liquid Epoxy Resin Composition) The viscosity (unit: Pa s) of each prepared resin composition was measured under the same conditions as the above "Viscosity of composition at 25°C" except that the rotation speed was 2 revolutions per minute. The thixotropic index (TI) of the composition was calculated by dividing this viscosity by the above "Viscosity of composition at 25°C". The results are shown in Table 1.
[0109] (Viscosity of liquid epoxy resin composition at 120°C) Using a MARS rheometer manufactured by HAAKE, the viscosity (unit: Pa s) of each resin composition produced was measured at 120°C after applying vibration at a frequency of 10 Hz for 40 seconds at 120°C in the oscillation strain control mode. The results are shown in Table 1.
[0110] (Gel time of liquid epoxy resin composition) Each liquid epoxy resin composition prepared was dropped to a size of about 5 mmΦ on a stainless steel plate heated to 120±2°C, and a metal needle was attached to the resin composition at regular intervals, and the time (unit: seconds) until the stringiness disappeared was measured with a stopwatch. In addition, in the liquid epoxy resin composition of the present invention, the gel time is preferably 30 to 600 seconds, more preferably 60 to 570 seconds, and particularly preferably 90 to 540 seconds. When the gel time is within this range, poor injectability due to gelation of the liquid epoxy resin composition can be suppressed, and the molding time during compression molding is not too long, thereby improving productivity.
[0111] (Evaluation of injectability of liquid epoxy resin composition) A silicon chip (length: 18 mm, width: 18 mm, thickness: 300 μm) was placed on a silicon wafer (diameter 300 mm, thickness 760 μm) with nine spacers (disk-shaped with diameter 1 to 2 mm, thickness 20 μm) between them. The spacers were arranged at equal intervals on the diagonal of the silicon chip (see Figure 2 (B)). In this manner, four silicon chips were arranged at equal intervals near the outer periphery of the silicon wafer (see Figure 2 (A)).
[0112] This silicon wafer, together with the silicon chip and spacer, was placed in a compression molding device (model number: WCM-300, manufactured by Apic Yamada Co., Ltd.) equipped with a mold. Next, the mold was filled with a liquid epoxy resin composition, and compression molding was performed under conditions of a temperature of 120°C and a pressure of 250 kN. The liquid epoxy resin composition was then cured by heating at this temperature for 400 seconds, thereby forming a 500 μm-thick layer of the cured liquid epoxy resin composition (in which the silicon chip and spacer were encapsulated) that covered the entire silicon wafer.
[0113] The silicon wafer covered with the layer of the cured product was removed from the compression molding device and cut at a position slightly away from the outer edge of the silicon chip to obtain a sealing product. The silicon chip, the cured product, and the spacer were removed from the sealing product by flat surface polishing until the thickness of the layer of the cured product measured from the silicon wafer was about 10 μm, to obtain a test piece for evaluating the injectability. The polished side of the obtained test piece was observed visually or under a microscope (magnification: 100 times). If no voids were observed in the test piece, or if the maximum width of the voids observed in the test piece was less than 100 μm, the injectability was evaluated as ○ (see FIG. 3(B)), and if the maximum width of the voids observed in the test piece was 100 μm or more, the injectability was evaluated as × (see FIG. 3(A)).
[0114] (Preparation of cured product) Each of the prepared resin compositions was heated in a dryer at 150° C. for 1 hour to obtain a cured product.
[0115] (Thermal conductivity of the cured product) Each prepared resin composition was used to obtain a cured product by the method described in the section "Preparation of Cured Product". The obtained cured product was processed to prepare a test piece (length 10 mm, width 10 mm, thickness 0.7 mm). The thermal conductivity of the obtained test piece was measured by the xenon flash (Xe-flash) method using a thermal conductivity measuring device (LFA447 Nanoflash, manufactured by NETZSCH).
[0116] (Bias HAST test of cured product) FIG. 4 shows a schematic diagram of the comb-shaped electrode used in the evaluation of insulation reliability by bias HAST test. This comb-shaped electrode is composed of a polyimide film substrate (thickness 38 μm) and copper wiring patterned thereon (wiring width 15 μm, line pitch 30 μm, thickness 8 μm, tin-plated (thickness 0.2 ± 0.05 μm)). A liquid epoxy resin composition was applied to this comb-shaped electrode to a thickness of 150 μm, and the liquid epoxy resin composition on the comb-shaped electrode was cured by heating at 150 ° C. for 1 hour using a dryer to obtain a test piece. This test piece was mounted in a HAST device (model number: PC-422R8, Hirayama Manufacturing Co., Ltd.), and the electrical resistance value was continuously monitored under conditions of relative humidity 85% and temperature 130 ° C. with a bias voltage of 3.5 V applied, and the time (unit: hr) from the start of the test until a short circuit occurred (electrical resistance value became 10 kΩ or less) was measured. The results are shown in Table 1.
[0117] (Chloride ions in the hardened material (Cl - ) content Each prepared resin composition was heated at 150°C for 1 hour to harden the resulting sample, which was then crushed into pieces of about 5 mm square. 2.5 g of this sample was added to 25 cm of ion-exchanged water. 3 The extract was added to the sample and placed in a PCT test tank (EHS-221M, manufactured by Espec Corporation, tank at 121°C±2°C / humidity 100% / 2atm) for 20 hours, and then cooled to room temperature to obtain the test solution. The chloride ion concentration of the test solution obtained by the above procedure was measured using an ion chromatograph (Prominence HIC-NS, manufactured by Shimadzu Corporation, column IC-A1 used). The evaluation results of the chloride ion content are shown in Table 1.
[0118] [Table 1]
[0119] As is clear from Table 1, in a liquid epoxy resin composition containing (A) epoxy resin (including an aliphatic epoxy resin represented by formula (I)), (B) curing agent, (C) inorganic filler, and (D) carbon black, when the inorganic filler (C) contains an alumina filler having an appropriate average particle size in combination with a silica filler, and the content of (D) carbon black is appropriate, the liquid epoxy resin composition gave a cured product having a high thermal conductivity of 0.8 W / m K or more (Examples 1 to 7 and Reference Examples 1 to 4). In electronic components manufactured using such liquid epoxy resin compositions as a mold underfill material for TSV, the release of heat generated during operation is improved. In contrast, the cured product obtained from a liquid epoxy resin composition not containing an alumina filler had low thermal conductivity (Comparative Example 1). In electronic components manufactured using such a liquid epoxy resin composition as a mold underfill material for TSV, the heat generated during operation cannot be sufficiently dissipated.
[0120] In the liquid epoxy resin composition prepared using epoxy resin (A) having a relatively low chloride ion content, the amount of chloride ions detected was inevitably small (Reference Example 2). In the cured product obtained from such a liquid epoxy resin composition, the time until a short circuit occurred was relatively long in the bias HAST test. When an ion trapping agent (E) was added to such a liquid epoxy resin composition, the amount of detected chloride ions further decreased, and the time until a short circuit occurred in the cured product obtained from such a liquid epoxy resin composition was extended in the bias HAST test (Examples 1 to 7 and Reference Example 4). However, when the ion trapping agent (E) was a hydrotalcite-based ion trapping agent, the time until a short circuit occurred did not change significantly (Reference Example 3). Furthermore, when the particle size of the ion trapping agent (E) was large, the injectability of the liquid epoxy resin composition decreased, although the viscosity did not increase significantly (Reference Example 4). On the other hand, in a liquid epoxy resin composition prepared using epoxy resin (A) with a relatively high chloride ion content, a large amount of chloride ions was detected even when ion-trapping agent (E) was added (Reference Example 1). In a cured product obtained from such a liquid epoxy resin composition, the time until a short circuit occurred was shortened in a bias HAST test. Although not shown in Table 2, the liquid epoxy resin composition in which the alumina filler in the inorganic filler (C) is surface-treated with a silane coupling agent having a methacryloxy group was superior in injectability and reduction of warpage compared to the liquid epoxy resin composition in which the alumina filler is surface-treated with a silane coupling agent having a phenylamino group. [Industrial Applicability]
[0121] The liquid epoxy resin composition of the present invention gives a cured product with high thermal conductivity. Therefore, electronic components manufactured using the liquid epoxy resin composition of the present invention as a molded underfill material for TSVs can fully release heat generated during operation even if the distance between the chip and wafer or between the chips is short. In a semiconductor device including such electronic components, performance degradation due to heat is suppressed. In addition, electronic components including a cured product obtained by curing the liquid epoxy resin composition of the present invention do not short circuit for a long period of time in a bias HAST test. Therefore, electronic components manufactured using the liquid epoxy resin composition of the present invention as a molded underfill material for TSVs show sufficient reliability even if the distance between bumps is short. Therefore, the liquid epoxy resin composition of the present invention is extremely suitable for use as a molded underfill material for TSVs. [Explanation of symbols]
[0122] 10 Silicon Wafer 11 Silicon chip 12. Bump 13 Mold underfill material for TSV 14 Mold 20 Silicon wafers (diameter 300 mm) 21 Silicon chip 22 Spacer (thickness 20 μm) 23 Cured product of molded underfill material for TSV 30 Cured mold underfill material for TSV 31 Spacer 32 Void
Claims
1. A liquid epoxy resin composition for use as a mold underfill material for a TSV, comprising the following (A) to (D): (A) epoxy resin; (B) a curing agent; (C) an inorganic filler consisting of a silica filler and an alumina filler; and (D) Carbon black Including, The epoxy resin (A) is represented by the following formula (I): 【Chemistry 4】 [In the formula, n is an integer from 1 to 15.] The epoxy resin includes an aliphatic epoxy resin represented by The average particle size of the alumina filler is 0.1 μm to 0.3 μm; the content of the carbon black (D) is 0.1 parts by mass or more and 1.5 parts by mass or less when the mass of the epoxy resin (A) is 100 parts by mass, A liquid epoxy resin composition that gives a cured product having a thermal conductivity of 0.8 W / m·K or more and less than 1.2 W / m·K.
2. (E) further comprising an ion trapping agent; Chloride ion (Cl - ) is 0.01 ppm or more and less than 2.5 ppm based on the total mass of the liquid epoxy resin composition, The content of the chloride ions is such that the concentration of the cured product of the liquid epoxy resin composition crushed into 5 mm squares is 0.1 g / cm 3 2. The liquid epoxy resin composition according to claim 1, wherein the viscosity is measured by a method comprising the steps of: immersing the liquid epoxy resin composition in water for 20 hours under conditions of a temperature of 121° C., a humidity of 100% and 2 atm; and subjecting the extract obtained to ion chromatography.
3. 3. The liquid epoxy resin composition according to claim 2, wherein the ion trapping agent (E) comprises at least one selected from the group consisting of a bismuth-based compound, a zirconium-based compound, and an antimony-based compound.
4. 3. The liquid epoxy resin composition according to claim 2, wherein the average particle size of the ion trapping agent (E) is 0.01 μm to 2 μm.
5. The total chlorine content of the aliphatic epoxy resin represented by formula (I) is 3000 ppm or less, 2. The liquid epoxy resin composition according to claim 1, wherein the epoxy resin (A) contains, in combination with the aliphatic epoxy resin represented by formula (I), another epoxy resin having a total chlorine content of 3000 ppm or less.
6. 2. The liquid epoxy resin composition according to claim 1, wherein the content of the inorganic filler (C) is 50 to 90 parts by mass when the total mass of the liquid epoxy resin composition is 100 parts by mass.
7. 2. The liquid epoxy resin composition according to claim 1, wherein the epoxy resin (A) further contains an epoxy resin having an aromatic ring in the molecule.
8. 2. The liquid epoxy resin composition according to claim 1, wherein the (B) curing agent comprises at least one member selected from the group consisting of phenolic compounds and nitrogen-containing heterocyclic compounds.
9. 2. The liquid epoxy resin composition according to claim 1, further comprising (F) a silicone additive.
10. 2. The liquid epoxy resin composition according to claim 1, further comprising (G) a coupling agent.
11. 2. The liquid epoxy resin composition according to claim 1, wherein the content of particles having a particle size of more than 1 μm in the inorganic filler (C) is less than 1.0 part by mass when the total mass of the inorganic filler (C) is 100 parts by mass.
12. 2. The liquid epoxy resin composition according to claim 1, wherein the alumina filler is surface-treated with a silane coupling agent having a methacryloxy group or a phenylamino group.
13. A semiconductor package having a semiconductor element encapsulated with the liquid epoxy resin composition according to claim 1.
Citation Information
Patent Citations
Epoxy resin composition for sealing semiconductor, and semiconductor device
JP2017179185A
Epoxy resin composition for sealing semiconductor, and semiconductor device
JP2021172793A
Mold underfill composition for TSV
JP2023109410A
Sealing composition and semiconductor device
WO2019131670A1